Politics at the airport - Salter, Mark B. (University of Minnesota Press, 2008)
"Politics at the Airport brings together leading scholars to examine how airports both shape and are shaped by current political, social, and economic conditions. Focusing on the ways that airports have become securitized, the essays address a wide range of practices and technologies--from architecture, biometric identification, and CCTV systems to 'no-fly lists' and the privatization of border control--now being deployed to frame the social sorting of safe and potentially dangerous travelers. This provocative volume broadens our understanding of the connections among power, space, bureaucracy, and migration while establishing the airport as critical to the study of politics and global life"--Provided by publisher